Knowledge Management System Model for Learning Organisations - Yousif, Amin; Roshayu, Mohamad (2017)
Based on the literature of knowledge management (KM), this paper reports on the progress of developing a new knowledge management system (KMS) model with components architecture that are distributed over the widely-recognised socio-technical system (STS) aspects to guide developers for selecting the most applicable components to support their KM practice in learning organisations (LO). This new model will bridge the literature gap found in KMS components which are not clearly defined, nor arranged and categorised for the most efficient use inside the organisation. Without this model, KMS developers should expect deficiency in their design due to the possibility of missing or misinterpreting important components for the intended design. Therefore, with this new model, the much clearer approach is achieved by ensuring that all KMS components are clearly identified and used to guarantee KMS effectiveness in the organisation. This research leads to a further study to test and confirm the new model for KMS development in LO’s.